Da criação como experimentação contínua: práticas de roteiro no cinema brasileiro contemporâneo - Dourado, Patrícia (2021)
This research investigates different screenwriting practices based on the process of creation studies of some filmmakers on contemporary Brazilian cinema. It is a complementary look concerning the observation of practices of a varied corpus. The filmmakers whose processes are studied are mainly: Eliane Caffé, Anna Muylaert and Leonardo Mouramateus; and, in addition: Marcelo Gomes, Karim Ainouz, Alê Abreu and Cao Guimarães. The screenwriter-director is the study focus of this research in order to concentrate on the transformations, adaptations and recreations that the screenplays undergo throughout the entire process of film creation, and sees in the diversity of contemporary Brazilian cinema a corpus capable of expressing the complexity of the screenwriting and narrative in cinema. The guiding question is "how can the complex approach of a varied corpus, in a study that does not separate film, process and spectator, contribute to a broader education in the field of screenwriting and narrative studies in cinema?". It finds theoretical and methodological support especially in Cecília Salles' theory of creation process, in dialogue with other theories, such as the filmmakers theory (Aumont, 2002; Penafria et al. 2016); the polycentric approach to world cinema (Nagib, 2006; Dennison, 2013); the procedural theory of narrative (Ricoeur, 2010); materialities of communication (Gumbrecht, 2010); and film literacy studies (Tavares & ReiaBaptista, 2019; Reia-Baptista, 2009). Also, It is fundamental for reflections on screenwriting practices the observations on the reading processes according to Vilém Flusser and Paulo Freire; the gesture of making and the need to pontificate (translate) in Vilém Flusser; and the contributions of Jacques Rancière on the ignorant schoolmaster and the emancipated spectator. It seeks what is complementary, more than what is similar or different, in the diversity of screenwriting creation procedures in a vision of creation as continuous experimentation, which remains active throughout the process, and which also extends to the spectator. It seeks to contribute to the fields of communication studies, semiotics; creation process; cinema; narrative; screenwriting; film literacy and the history of Brazilian and world cinema, in a across disciplines approach